Particle Transport in a 3D Duct by Adding and Doubling. Issue 3 (16th April 2017) - Ganapol, B. D.
ABSTRACT: How particles are transported through a duct by Lambertian reflection from duct walls is again considered. This popular transport example has been solved with most numerical transport methods except notably one—the method of adding and doubling. We shall show that the method of doubling provides every bit as, or more, accurate reflectances and transmittances as the numerical discrete ordinates and analytical discrete ordinates methods with generally less mathematical and numerical effort.